Economic Measurement in Public Welfare Economics: Practical Experiences on the Regional Level in Germany (Cultura Económica, 2019)
What is the fair price for social welfare? This paper shows that economic measurement performed in value-based markets may give an answer to this question. Economic measurement can do the same in very different fields of social work applying different methods, such as public bids or qualified bargaining. After giving a short theoretical overview, two German projects are presented and analyzed in detail. The paper presents how trading welfare expressed in terms of outcome may be established with positive effects for public finances as well as for the common good.
Keywords: PUBLIC FINANCES; ECONOMETRICS; COMMON BENEFIT; SOCIAL CARE